Analysis of Understanding the Concept of Alkenes through the Three-tier Multiple Choice Diagnostic Test Instrument - Selina Selina; Rini Muharini; Ira Lestari; Masriani Masriani; Rahmat Rasmawan (Postgraduate, University of Mataram, 2024)
The ability of prospective teacher students to master chemistry material will influence the achievement of learning objectives. Alkenes are an important sub material in organic chemistry courses because alkenes are often used as basic ingredients in chemical reactions. This research aims to analyze Untan chemistry education students' understanding of alkene sub materials. The research method used is quantitative descriptive. The research sample consisted of 50 students. The instrument used was Three-Tier Multiple Choice with a total of 10 questions and a semi-structured interview. Before using the instrument, a validity and reliability test was carried out first. The analysis results of students who understand the concept well are only 28.06%, and 6.06% of students understand but are not sure, while the percentage of students who do not understand the concept is 40.21%, and 29.95% of students experience misconceptions.